2020
DOI: 10.1016/j.heliyon.2020.e04158
|View full text |Cite
|
Sign up to set email alerts
|

Greater learning transfer effect for avoidance of loss than for achievement of gain in Finnish and Russian schoolchildren

Abstract: Classification of behavior into principal categories of approach and avoidance is grounded in evolutionary considerations and multiple results of behavioral, self-report, and brain-activity analyses. Contrasted via measures of cognitive processes, avoidance is accompanied by greater cognitive engagement than approach. Considering outcome as a key constituent of behavioral underpinnings, we interpret approach/avoidance distinction in terms of structure of experience: avoidance domain provides more detailed inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
(81 reference statements)
1
0
0
Order By: Relevance
“…Previous studies have suggested that reward and loss constitute independent components ( Fonagy and Luyten, 2018 ). Consistent with prior research, the present study found that longer response times and poorer accuracy to loss rather than reward stimuli were observed, suggesting that loss processing may have more complex cognitive components ( Sozinov et al, 2020 ). Meanwhile, similar to another study ( Goncalves et al, 2021 ), the present study observed that emotional responses under loss rather than reward anticipation appeared to be associated with SMAs in adolescents.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have suggested that reward and loss constitute independent components ( Fonagy and Luyten, 2018 ). Consistent with prior research, the present study found that longer response times and poorer accuracy to loss rather than reward stimuli were observed, suggesting that loss processing may have more complex cognitive components ( Sozinov et al, 2020 ). Meanwhile, similar to another study ( Goncalves et al, 2021 ), the present study observed that emotional responses under loss rather than reward anticipation appeared to be associated with SMAs in adolescents.…”
Section: Discussionsupporting
confidence: 90%